Nuclear receptors in the cross-talk of drug metabolism and inflammation. (February 2013) - Gerbal-Chaloin, Sabine; Iankova, Irena; Maurel, Patrick; Daujat-Chavanieu, Martine
<x xml:space="preserve">Abstract</x> Inflammation and infection have long been known to affect the activity and expression of enzymes involved in hepatic and extrahepatic drug clearance. Significant advances have been made to elucidate the molecular mechanisms underlying the complex cross-talk between inflammation and drug-metabolism alterations. The emergent role of ligand-activated transcriptional regulators, belonging to the nuclear receptor (NR) superfamily, is now well established. The NRs, pregnane X receptor, constitutive androstane receptor, retinoic X receptor, glucocorticoid receptor, and hepatocyte nuclear factor 4, and the basic helix-loop-helix/Per-ARNT-Sim family member, aryl hydrocarbon receptor, are the main regulators of the detoxification function. According to the panel of mediators secreted during inflammation, a cascade of numerous signaling pathways is activated, including nuclear factor kappa B, mitogen-activated protein kinase, and the Janus kinase/signal transducer and activator of transcription pathways. Complex cross-talk is established between these signaling pathways regulating either constitutive or induced gene expression. In most cases, a mutual antagonism between xenosensor and inflammation signaling occurs. This review focuses on the molecular and cellular mechanisms implicated in this cross-talk.